Adsorbent for hydrocarbon recovery with improved mechanical properties

By using an amorphous silica adsorbent bed with high relative micropore surface area and crushing strength, combined with the temperature-changing adsorption process, the problem of low removal efficiency of heavy hydrocarbons in the prior art is solved, and efficient natural gas purification effect is achieved.

CN119136892APending Publication Date: 2024-12-13BASF CORPORATON
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037964.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-04
Filing Date
2023-04-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing silica-based adsorbents are less efficient when removing heavy hydrocarbons from natural gas, and it is necessary to explore higher affinity adsorbent materials to improve adsorption efficiency.

Method used

Adsorbent particles containing amorphous silica, adsorbent beds with high relative micropore surface area and crushing strength, remove heavy hydrocarbons and water from natural gas through a temperature variable adsorption process, and release adsorbed components using a high temperature regeneration step. .

Benefits of technology

It significantly improves the removal efficiency of heavy hydrocarbons, can achieve lower final concentrations at lower initial concentrations, and is suitable for natural gas purification and other industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136892A_ABST
    Figure CN119136892A_ABST
Patent Text Reader

Abstract

Disclosed in certain embodiments are adsorbents having improved mechanical properties for capturing heavy hydrocarbons during, for example, a temperature swing adsorption process.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 338,384, filed on May 4, 2022, the disclosure of which is hereby incorporated by reference in its entirety. Background Art

[0003] Hydrocarbons are often removed from natural gas to prevent condensation of liquids in pipeline transportation systems. Pipelines are often set to dew point specifications to prevent condensation of liquids, with hydrocarbon recovery units (HRUs) used to specifically remove heavy hydrocarbons.

[0004] Silica-based adsorbents have an affinity for heavy hydrocarbons such as C5+ components and can be used in HRUs. In such systems, a fluid volume (e.g., natural gas) containing heavy hydrocarbons is passed through a silica gel bed to capture the heavy hydrocarbons. Regeneration can be performed by passing a pressurized and / or heated natural gas feed stream or product gas stream through an adsorbent bed. After cooling, the heavy hydrocarbons contained in the effluent from the regeneration process can be condensed and removed as a liquid product. In order to improve the adsorption efficiency of such systems, it is necessary to explore the use of other adsorbent materials that exhibit a higher affinity for heavy hydrocarbons. Summary of the invention

[0005] A simplified overview of various aspects of the disclosure is presented below to provide a basic understanding of such aspects. This overview is not an extensive review of the disclosure. It is neither intended to identify the key or important elements of the disclosure, nor to describe any scope of the specific embodiments of the disclosure or any scope of the claims. Its sole purpose is to present some concepts of the disclosure in a simplified form as a preface to a more detailed description presented later.

[0006] One aspect of the present disclosure relates to sorbent particles comprising amorphous silica.

[0007] In at least one embodiment, the relative micropore surface area (RMA) of the adsorbent particles is at least about 15%, and the total pore volume of the adsorbent particles for pores with diameters between 500 nm and 20,000 nm is less than 5 mm 3 / g, as measured by mercury porosimetry.

[0008] In at least one embodiment, the relative micropore surface area (RMA) of the sorbent particles is at least about 15%, and the average crush strength of the sorbent particles is greater than about 60 N / bead.

[0009] In at least one embodiment, the relative micropore surface area (RMA) of the sorbent particles is at least about 15%, and the tapped bulk density of the sorbent particles is greater than 0.6 g / cm3 .

[0010] In at least one embodiment, the relative micropore surface area (RMA) of the sorbent particles is at least about 15%, and the tapped bulk density of the sorbent particles is greater than 0.6 g / cm 3 , and the total pore volume of the adsorbent particles for pores with diameters between 500 nm and 20,000 nm is less than 200 mm 3 / g, as measured by mercury porosimetry.

[0011] In at least one embodiment, the total pore volume for pores with diameters between 500 nm and 20,000 nm, as measured by mercury porosimetry, is less than about 4 mm 3 / g, less than about 3mm 3 / g, less than about 2mm 3 / g, less than about 1mm 3 / g, less than about 0.5mm 3 / g, or less than about 0.1mm 3 / g.

[0012] In at least one embodiment, the tapped bulk density of the adsorbent particles is at least 0.65 g / cm 3 , at least about 0.7 g / cm 3 , at least about 0.75 g / cm 3 , at least about 0.8 g / cm 3 , at least about 0.9 g / cm 3 , or at least about 1.0 g / cm 3 .

[0013] In at least one embodiment, the RMA of the sorbent particles is at least about 20%, at least about 25%, or at least about 30%.

[0014] In at least one embodiment, the sorbent particles have a particle size of at least about 600 m 2 / g, at least about 700m 2 / g, at least about 800m 2 / g, at least about 900m 2 / g, or at least about 1000m 2 / g of fluid-accessible average Brunauer-Emmett-Teller (BET) surface area.

[0015] In at least one embodiment, the average diameter of the sorbent particles is greater than about 1 mm, greater than about 2 mm, greater than about 3 mm, greater than about 4 mm, or from about 2 mm to about 4 mm.

[0016] In at least one embodiment, the sorbent particles contain SiO2 in an amount of at least about 80 wt.%, at least about 85 wt.%, at least about 90 wt.%, at least about 95 wt.%, or at least about 99 wt.%, or at least about 99.9 wt.%, or at least about 99.99 wt.%, on average based on the total weight of the sorbent particles.

[0017] In at least one embodiment, the sorbent particles further comprise alumina.

[0018] Another aspect of the present disclosure relates to a system configured to treat a fluid substance. In at least one embodiment, the system includes a sorbent bed comprising the sorbent particles of any of the preceding claims.

[0019] In at least one embodiment, the system is a temperature swing adsorption system.

[0020] In at least one embodiment, the temperature swing adsorption system is suitable for adsorbing water and / or C5+ or C6+ components from a fluid substance. In at least one embodiment, the C5+ or C6+ components include one or more of pentane, hexane, benzene, heptane, octane, nonane, toluene, ethylbenzene, xylene, or neopentane.

[0021] Another aspect of the present disclosure relates to a natural gas purification system, comprising an adsorbent bed comprising the adsorbent particles of any of the preceding embodiments.

[0022] Another aspect of the present disclosure relates to an adsorbent bed comprising the adsorbent particles of any of the preceding embodiments.

[0023] Another aspect of the present disclosure relates to a method of treating a fluid material comprising an initial concentration of a C5+ or C6+ component, the method comprising contacting the fluid material with the adsorbent particles of any of the preceding embodiments. In at least one embodiment, the C5+ or C6+ component comprises one or more of pentane, hexane, benzene, heptane, octane, nonane, toluene, ethylbenzene, xylene, or neopentane. In at least one embodiment, the C5+ or C6+ component comprises one or more of n-C6, n-C7, n-C8, n-C9, or benzene. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present disclosure is illustrated by way of example and not limitation in the figures of the accompanying drawings in which:

[0025] Figure 1 depicts an illustrative sorbent bed according to an embodiment of the present disclosure;

[0026] Figure 2 A method for removing heavy hydrocarbons from a fluid substance according to an embodiment of the present disclosure is illustrated; and

[0027] Figure 3 Breakthrough curves for various inventive and comparative adsorbents are shown. DETAILED DESCRIPTION

[0028] The present disclosure generally relates to an adsorbent for improved gas stream purification, and a system incorporating the adsorbent and methods of using the same. More specifically, the present disclosure relates to an adsorbent for removing heavy hydrocarbons (e.g., C5+ or C6+ components), water, acid gases, or other chemicals and recovering the heavy hydrocarbons by using an integrated process.

[0029] The adsorption process disclosed herein for removing heavy hydrocarbons (e.g., C5+ or C6+ components) or other combinations (e.g., water) from a gas feed stream (e.g., a natural gas feed stream) can be achieved by temperature swing adsorption (TSA). TSA processes are generally known in the art for various types of adsorption separations. Typically, TSA processes utilize process steps of adsorption at low temperatures, regeneration with a hot purge gas at high temperatures, and subsequent cooling to the adsorption temperature. TSA processes are typically used for drying gases and liquids and for purification to remove trace impurities. TSA processes are typically used when the components to be adsorbed are strongly adsorbed on the adsorbent, and therefore regeneration requires heat.

[0030] A typical TSA process includes an adsorption cycle and a regeneration (desorption) cycle, each cycle can include multiple adsorption steps and regeneration steps, as well as cooling steps and heating steps. The regeneration temperature is higher than the adsorption temperature to achieve desorption of water, methanol and heavy hydrocarbons. For illustration, during the first adsorption step of adsorbing C5+ or C6+ components from a gas stream (e.g., a raw natural gas feed stream) using an adsorbent, in some embodiments, the temperature is maintained at less than 150°F (66°C), and in other embodiments from about 60°F (16°C) to about 120°F (49°C). In the regeneration step of the present disclosure, water and C5+ or C6+ components adsorbed in the adsorbent bed are initially released from the adsorbent bed, thereby regenerating the adsorbent at a temperature of from about 300°F (149°C) to about 550°F (288°C) in some embodiments.

[0031] In the regeneration step, a portion of one of the gas streams (e.g., a natural gas stream), the product effluent from the adsorber unit, or a waste stream from a downstream process can be heated and the heated stream circulated through the adsorbent bed to desorb the adsorbed components. In some embodiments, it is advantageous to regenerate the adsorbent using a hot purge stream comprising a heated raw natural gas stream.

[0032] In some embodiments, the pressure used during the adsorption and regeneration steps is generally elevated to typically 700 to 1500 psig. Typically, heavy hydrocarbon adsorption is conducted at a pressure close to the feed stream pressure, and the regeneration step can be conducted at about the adsorption pressure or at reduced pressure. When a portion of the adsorption effluent stream is used as a purge gas, regeneration can advantageously be conducted at about the adsorption pressure, especially when the waste stream or purge stream is, for example, reintroduced into the raw natural gas stream.

[0033] Although the embodiments of the present disclosure are described with respect to natural gas purification processes, it should be understood by those skilled in the art that the embodiments herein may be used or adapted for use in other types of industrial applications other than LGN and natural gas liquids (NGL) applications that require heavy hydrocarbon and / or water removal.

[0034] Figure 1 An adsorber unit 100 is illustrated according to an embodiment of the present disclosure, which may be suitable for use in a TSA process. In some embodiments, the adsorber unit 100 includes a single container 102 that houses an adsorbent bed 101. Other embodiments may utilize multiple containers and adsorbent beds, for example, when a continuous TSA process is implemented, where one or more adsorbent beds are subjected to an adsorption cycle while one or more beds are subjected to a regeneration cycle. For example, in some embodiments, the adsorber unit 100 may include two or more containers and adsorbent beds that are replicas of the container 102 and the adsorbent bed 101 (not shown). When the adsorbent bed 101 is subjected to an adsorption cycle, the duplicate adsorbent bed is subjected to a regeneration cycle, for example, using the product gas produced by the adsorption cycle performed by the adsorbent bed 101.

[0035] The adsorbent bed 101 includes an adsorbent layer 110 and an adsorbent layer 120, each contained within a container 102. The flow direction indicates the flow of the gas feed stream through the inlet of the container 102, through the adsorbent layer 110, and then through the adsorbent layer 120 before reaching the outlet of the container 102. Based on this flow direction, the adsorbent layer 120 is referred to as downstream of the adsorbent layer 110. In some embodiments, each adsorbent layer may include its corresponding adsorbent in the form of adsorbent beads having a diameter of, for example, about 1 mm to about 5 mm. The relative sizes of the adsorbent layers are not necessarily drawn to scale, although in certain embodiments, the weight percentage (wt.%) of the adsorbent layer 120 relative to the total weight of the adsorbent bed 101 (i.e., the total weight of the adsorbent layer agent 120, the adsorbent layer agent 110, and any additional layers) may be greater than 50 wt.%, greater than 60 wt.%, greater than 70 wt.%, greater than 80 wt.%, or greater than 90 wt.%. In some embodiments, adsorbent layer 110 is omitted, and adsorbent layer 120 is the only adsorbent layer in the adsorbent bed 101 .

[0036] In some embodiments, the adsorbent layer 110 comprises a water-stable adsorbent such as Durasorb TM HD (available from BASF), contains, for example, silica or silica-alumina.

[0037] In some embodiments, the adsorbent layer 120 comprises a microporous adsorbent having a preferential selectivity for C5+ or C6+ hydrocarbons. As used herein, the term "preferentially selective for" or "selective for" indicates that the adsorbent adsorbs a particular compound at a greater equilibrium loading than methane, further described by the following equation (for C6+): Selectivity = (Loading C6+ / Concentration C6+) / (Loading C1 / Concentration C1), where C1 is methane, and where loading is defined as the number of moles of adsorbed component / gram of adsorbent. In certain embodiments, the C5+ or C6+ compound may comprise one or more of pentane, hexane, benzene, heptane, octane, nonane, toluene, ethylbenzene, xylene, or neopentane.

[0038] As used herein, the term "microporous adsorbent" refers to an adsorbent material having a relative microporous surface area (RMA) of at least about 10%, at least about 15%, at least about 20%, at least about 25%, or at least about 30%, which is the ratio of the microporous surface area to the Brunauer-Emmett-Teller (BET) surface area. The microporous adsorbent may further have one or more of the following properties: a total pore volume of at least about 5 mm2 for pores with diameters between 500 nm and 20,000 nm as measured by mercury porosimetry; 3 / g, at least about 10mm 3 / g, at least about 20mm 3 / g, at least about 30mm 3 / g, at least about 40mm 3 / g, at least about 45mm 3 / g, or at least about 50mm 3 / g, or alternatively, less than about 5 mm 3 / g, not more than about 4mm 3 / g, not more than about 3mm 3 / g, not more than about 2mm 3 / g, or not more than about 1mm 3 / g; at least about 0.40cm 3 / g, about 0.40cm 3 / g to about 0.50cm 3 / g, or about 0.425 cm 3 / g to about 0.475cm 3 / g pore volume (e.g., Barrett-Joyner-Halenda (BJH) pore volume); or at least about 400 m 2 / g, at least about 500m 2 / g, at least about 600m 2 / g, at least about 700m 2 / g, at least about 800m 2 / g, or at least about 900m 2 / g of BET surface area.

[0039] As used herein, "micropore surface area" refers to the total surface area associated with pores having a diameter of less than 200 angstroms. In some embodiments, the micropore surface area of ​​the microporous adsorbent is at least about 40 m 2 / g, at least about 50m 2 / g, at least about 100m 2 / g, at least about 150m 2 / g, at least about 200m 2 / g, or at least about 230m 2 / g. In some embodiments, the microporous surface area of ​​the microporous adsorbent is about 40 m 2 / g to about 300m 2 / g, about 50m 2 / g to about 300m 2 / g, about 100m 2 / g to about 300m 2 / g, about 150m 2 / g to about 300m 2 / g, about 200m 2 / g to about 300m 2 / g, or about 230m 2 / g to about 300m 2 / g. In some embodiments, the relative micropore surface area is about 5% to about 10%, about 10% to about 15%, about 15% to about 20%, about 20% to about 25%, about 25% to about 30%, or any range defined therein (e.g., about 15% to about 25%). In some embodiments, the range of the corresponding BET surface area of ​​the microporous adsorbent is about 650 m 2 / to about 850m 2 / g.

[0040] In some embodiments, the microporous adsorbent comprises at least about 85 wt.%, at least about 90 wt.%, at least about 95 wt.%, at least about 96 wt.%, at least about 97 wt.%, at least about 98 wt.%, at least about 99 wt.%, at least about 99.9 wt.%, or at least about 99.99 wt. wt.% silicon dioxide (SiO2) based on the total weight of the microporous adsorbent. In some embodiments, the microporous adsorbent further comprises up to 20 wt.% (i.e., greater than about 0 wt.% to about 20 wt.%), up to about 15 wt.%, up to about 10 wt.%, up to about 9 wt.%, up to about 8 wt.%, up to about 7 wt.%, up to about 6 wt.%, up to about 5 wt.%, up to about 4 wt.%, up to about 3 wt.%, up to about 2 wt.%, or up to about 1 wt.% aluminum oxide (Al2O3). In at least one embodiment, one or more of SiO 2 or Al 2 O 3 (if present) is amorphous (eg, completely amorphous).

[0041] In some embodiments, the total pore volume of the microporous adsorbent for pores with diameters between 500 nm and 20,000 nm is at least about 20 mm 3 / g, at least about 40mm 3 / g, at least about 70mm 3 / g, at least about 100mm 3 / g, at least about 120mm 3 / g, at least about 140mm 3 / g, at least about 150mm 3 / g, at least about 160mm 3 / g, or at least about 170mm 3 In some embodiments, the total pore volume of the microporous adsorbent for pores with diameters between 500 nm and 20,000 nm is about 20 mm 3 / g to about 200mm 3 / g, about 40mm 3 / g to about 200mm 3 / g, about 70mm 3 / g to about 200mm 3 / g, about 100mm 3 / g to about 200mm 3 / g, about 120mm 3 / g to about 200mm 3 / g, about 140mm 3 / g to about 200mm 3 / g, about 150mm 3 / g to about 200mm 3 / g, about 160mm 3 / g to about 200mm 3 / g, about 170mm 3 / g to about 200mm 3 In some embodiments, the total pore volume of the microporous adsorbent for pores with diameters between 500 and 20,000 nm is less than about 5 mm 3 / g, for example, not more than about 4 mm 3 / g, not more than about 3mm 3 / g, not more than about 2mm 3 / g, not more than about 1mm 3 / g, or any range defined therein (e.g., 1 mm 3 / g to 3mm 3 In at least some embodiments, the total pore volume of the microporous adsorbent for pores with diameters between 500 nm and 20,000 nm is 0 mm 3 / g or below the detectable level.

[0042] In at least one embodiment, the total pore volume for pores with diameters between 500 and 20,000 nm is about 1 mm 3 / g, about 2mm 3 / g, about 3mm 3 / g, about 4mm 3 / g, about 5mm 3 / g, about 6mm 3 / g, about 7mm 3 / g, about 8mm 3 / g, about 9mm 3 / g, about 10mm 3 / g, about 11mm 3 / g, about 12mm 3 / g, about 13mm 3 / g, about 14mm 3 / g, about 15mm 3 / g, about 16mm 3 / g, about 17mm 3 / g, about 18mm 3 / g, about 19mm 3 / g, about 20mm 3 / g, about 21mm 3 / g, about 22mm 3 / g, about 23mm 3 / g, about 24mm 3 / g, about 25mm 3 / g, about 26mm 3 / g, about 27mm 3 / g, about 28mm 3 / g, about 29mm 3 / g, about 30mm 3 / g, or any range defined therein (e.g., about 1 mm 3 / g to about 20mm 3 / g).

[0043] In some embodiments, the microporous adsorbent comprises a fluid accessible surface area characterized by about 400 m 2 / g to about 1000m 2 / g, about 500m 2 / g to about 1000m 2 / g, about 600m 2 / g to about 1000m 2 / g, about 700m 2 / g to about 1000m 2 / g, about 800m 2 / g to about 1000m 2 / g, about 900m 2 / g to about 1000m 2 / g, or a BET surface area within any range defined therebetween.

[0044] In some embodiments, the tapped bulk density of the microporous adsorbent is less than 6 g / cm 3 In some embodiments, the tapped bulk density of the microporous adsorbent is at least 0.65 g / cm 3 , at least about 0.7 g / cm 3 , at least about 0.75 g / cm 3 , at least about 0.8 g / cm 3 , at least about 0.85 g / cm 3 , at least about 0.9 g / cm 3 , at least about 0.95 g / cm 3 , at least about 1.0 g / cm 3 , or within any range defined therein.

[0045] In some embodiments, the microporous adsorbent has a BJH pore volume of at least about 0.40 cm 3 / g, about 0.40cm 3 / g to about 0.50cm 3 / g, or about 0.425 cm 3 / g to about 0.485cm 3 / g.

[0046] In some embodiments, the microporous adsorbent is in the form of spherical particles having an average diameter of, for example, at least about 1 mm, at least about 2 mm, at least about 3 mm, at least about 4 mm, about 2 mm to about 4 mm, or about 2.5 mm to about 3.5 mm.

[0047] In some embodiments, when in the form of spherical particles or "beads", the microporous adsorbent exhibits a crush strength of at least about 50 Newtons (N) / bead, at least about 60 N / bead, at least about 70 N / bead, at least about 80 N / bead, at least about 90 N / bead, at least about 100 N / bead, at least about 125 N / bead, at least about 150 N / bead, at least about 175 N / bead, at least about 200 N / bead, at least about 225 N / bead, at least about 250 N / bead, at least about 275 N / bead, or any range defined therein (e.g., about 70 N / bead to about 200 N / bead). The measurement of crush strength is intended to provide an indication of the ability of the adsorbent to maintain its physical integrity during handling and use. As discussed herein, crushing strength is determined using a tablet hardness tester (e.g., ERWEKA TBH 125) according to DIN 8948 (Section 7.3). For a given adsorbent, a representative sample of 25 intact beads of different sizes (diameter from about 2 mm to about 5 mm) is used. The beads are then crushed using a tablet hardness tester and the required force is determined. One bead is measured at a time, where a compressive force is applied at a rate of 25 N / s and a speed of 2.3 mm / s until the bead is crushed. The crushed beads are then removed, and the process is repeated for each subsequent bead. The average of the 25 beads is calculated to obtain the crushing strength of a given adsorbent.

[0048] In an exemplary embodiment, a microporous adsorbent that can be advantageously used, for example, in a TSA process has the following properties: about 740 m 2 / g to about 820m 2 / g of fluid accessible BET surface area; about 180m 2 / g to about 230m 2 / g micropore surface area; about 22% to about 30% RMA; about 0.42mL / g to about 0.49mL / g BJH pore volume; less than 6mm 3 / g (e.g., about 5 mm 3 / g to about 6mm 3 / g, less than about 5mm 3 / g, or less than 5mm 3 / g) of macropore volume (i.e., pore volume for pores having diameters of 500 nm to 20,000 nm); a crush strength of greater than about 100 N / bead; a tapped bulk density of about 0.70 kg / L to about 0.8 kg / L; and at least about 99 wt.% of SiO2 in amorphous form, based on the total weight of the microporous adsorbent.

[0049] Figure 2 A method 200 for removing heavy hydrocarbons (e.g., C5+ or C6+ components) from a fluid substance according to an embodiment of the present disclosure is illustrated. At block 202, an adsorbent bed comprising a microporous adsorbent in the form of adsorbent particles is provided. In some embodiments, the adsorbent bed corresponds to Figure 1 The adsorbent bed 101 is described. In some embodiments, the adsorbent particles are formed Figure 1 Depicted adsorbent layer 120. In some embodiments, the adsorbent bed further comprises additional adsorbent layers, such as adsorbent layer 110.

[0050] At frame 204, fluid material is directed toward adsorbent bed and contacted with it. In certain embodiments, contact occurs in temperature swing adsorption system. Fluid material can have the initial concentration of C5+ or C6+ component (for example, be greater than the concentration of benzene and / or other components of 150ppm). In certain embodiments, the initial concentration of one or more of C5+ or C6+ component is greater than 150ppm, greater than 250ppm, greater than 500ppm, greater than 1000ppm, greater than 2000ppm or greater than 3000ppm. In certain embodiments, initial concentration is 150ppm to 4000ppm, 250ppm to 4000ppm, 500ppm to 4000ppm, 1000ppm to 4000ppm, 2000ppm to 4000ppm or 3000ppm to 4000ppm.

[0051] At frame 206, processed fluid material is directed to one or more downstream processes. The ultimate concentration of the C5+ or C6+ component of fluid material can be measured. In certain embodiments, the ultimate concentration of one or more of C5+ or C6+ components is less than 30ppm, less than 20ppm, less than 10ppm, less than 5ppm, less than 4ppm, less than 3ppm, less than 2ppm or less than 1ppm. For example, C5+ or C6+ components can comprise one or more of pentane, hexane, benzene, heptane, octane, nonane, toluene, ethylbenzene, dimethylbenzene or neopentane, and / or can comprise one or more of n-C6, n-C7, n-C8, n-C9 or benzene.

[0052] Illustrative Examples

[0053] The following examples are set forth to aid in understanding the present disclosure and these examples should certainly not be construed as specifically limiting the embodiments described and claimed herein. Such variations as will be within the purview of those skilled in the art including substitution of all equivalents now known or later developed for the disclosed embodiments and variations in formulation or minor variations in experimental design will be considered to fall within the scope of the embodiments incorporated herein.

[0054] Micropore surface area and BET surface area can be measured by nitrogen porosimetry using, for example, Micromeritics 2000 porosimetry system. Mercury porosimetry can be performed using, for example, ThermoScientific TM Pascal 140 / 240 porosimeter. An exemplary method for measuring pore volume can be performed according to ASTM D4284-12 (2017) e1, "Standard Test Method for Determining Pore Volume Distribution of Catalysts and Catalyst Carriers by Mercury Intrusion Porosimetry".

[0055] As discussed herein, tapped bulk density is measured according to EN ISO 787-11. To measure the tapped bulk density of the sample adsorbent, a representative sample of 250 mL is poured into a 250 mL graduated cylinder of a tapping machine (e.g., Avica tapped density tester SVM 12). In order to pour the sample into the graduated cylinder, a metal funnel is used to ensure that the sample is poured evenly. The size of the metal funnel depends on the bead size of the sample. Different funnels can be used for different sieve lines (e.g., 2050, 1650, etc.), as described in Section 7.6 of DIN 8948. The graduated cylinder is placed in a tapping machine and the sample is tapped 600 times. The volume is read accurately to 1 mL and the sample mass is measured by weighing. The volume after tapping is divided by the mass of the sample to obtain the tapped bulk density (in g / cm 3 ).

[0056] Characterization of adsorbents

[0057] Various adsorbents were characterized and are summarized in Table 1 below.

[0058] Inventive Examples 1 and 2 are silica-based microporous adsorbents prepared using a conventional oil drop method, which were modified to adjust parameters including BET surface area, micropore surface area, and macropore volume as would be understood by one of ordinary skill in the art.

[0059] Comparative Example 1 is a silica-based microporous adsorbent similar to the composition described in International Application Publication No. WO 2016205616 A1.

[0060] Comparative Example 2 is as H (BASF) is a commercially available silica-based adsorbent.

[0061] Each sample was subjected to a pre-treatment procedure involving heating in the range of 170°C to 250°C for approximately three hours.

[0062] As shown in Table 1, Inventive Examples 1 and 2 simultaneously exhibit high RMA, high crush strength, and high density while being substantially free of macropores having diameters of 500 to 20,000 nm.

[0063] Table 1: Adsorbent properties

[0064]

[0065] *For pores with diameters of 500-20000nm

[0066] Adsorption test

[0067] Adsorbent beds were prepared for each of Inventive Example 1, Comparative Example 1 (two separate runs, designated A and B), and Comparative Example 2, wherein each bed was loaded with 167 cc of its respective adsorbent. Each bed was fed 15.4 slpm of a gas containing 200 ppm of n-C6, 100 ppm of n-C7, 50 ppm of n-C8, and 50 ppm of benzene at a temperature of 25° C. and a pressure of 900 psia. The beds were loaded with 167 cc of Sorbead H. The gas concentration was measured at the outlet of the bed, and a breakthrough curve was generated and plotted on Figure 3 Inventive Example 1 exhibits a longer penetration time than the comparative example.

[0068] In the above description, many specific details, such as specific materials, dimensions, process parameters, etc., are described to provide a comprehensive understanding of the embodiments of the present disclosure. Specific features, structures, materials or characteristics can be combined in any suitable manner in one or more embodiments. The words "example" or "exemplary" are used in this article to mean used as an example, example, or example. Any aspect or design described as "example" or "exemplary" herein is not necessarily interpreted as being superior to or better than other aspects or designs. In fact, the use of the words "example" or "exemplary" is intended to present concepts in a concrete way.

[0069] As used in this application, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or". That is, unless stated otherwise or clear from the context, "X includes A or B" is intended to mean any of the natural inclusive permutations. That is, if X includes A; X includes B; or X includes both A and B, then "X includes A or B" is satisfied in any of the foregoing cases. Furthermore, the articles "a" and "an" as used in this application and the appended claims should generally be interpreted to mean "one or more" unless stated otherwise or clear from the context to be directed to the singular form.

[0070] References throughout this specification to "an embodiment," "some embodiments," or "one embodiment" mean that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, appearances of the phrases "an embodiment," "some embodiments," or "one embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment, and such references mean "at least one."

[0071] It should be understood that the above description is intended to be illustrative, not restrictive. After reading and understanding the above description, many other embodiments will be apparent to those skilled in the art. Therefore, the scope of the present disclosure should be determined with reference to the attached claims and the full scope of equivalents given by such claims.

Claims

1. A sorbent particle comprising amorphous silica, wherein: The relative micropore surface area (RMA) of the adsorbent particles is at least about 15%, and The total pore volume of these adsorbent particles for pores with diameters between 500 nm and 20,000 nm is less than 5 mm 3 / g, as measured by mercury porosimetry.

2. A sorbent particle comprising amorphous silica, wherein: The relative micropore surface area (RMA) of these adsorbent particles is at least about 15%, and The average crush strength of these sorbent particles is greater than about 60 N / bead.

3. A sorbent particle comprising amorphous silica, wherein: The relative micropore surface area (RMA) of these adsorbent particles is at least about 15%, and The tapped bulk density of these adsorbent particles is greater than 0.6 g / cm 3 .

4. A sorbent particle comprising amorphous silica, wherein: The relative micropore surface area (RMA) of these adsorbent particles is at least about 15%, and The tapped bulk density of these adsorbent particles is greater than 0.6 g / cm 3 The total pore volume of these adsorbent particles for pores with diameters between 500 nm and 20,000 nm is less than 200 mm 3 / g, as measured by mercury porosimetry.

5. The adsorbent particle according to any one of the preceding claims, wherein The total pore volume for pores with diameters between 500 nm and 20,000 nm, as measured by mercury porosimetry, is less than about 4 mm 3 / g, less than about 3mm 3 / g, less than about 2mm 3 / g, less than about 1mm 3 / g, less than about 0.5mm 3 / g, or less than about 0.1mm 3 / g.

6. The adsorbent particle according to any one of the preceding claims, wherein The tapped bulk density of these adsorbent particles is at least 0.65 g / cm 3 , at least about 0.7 g / cm 3 , at least about 0.75 g / cm 3 , at least about 0.8 g / cm 3 , at least about 0.9 g / cm 3 , or at least about 1.0 g / cm 3 .

7. The adsorbent particle according to any one of the preceding claims, wherein The RMA of the sorbent particles is at least about 20%, at least about 25%, or at least about 30%.

8. The sorbent particle according to any one of the preceding claims, wherein These adsorbent particles have a diameter of at least about 600 m 2 / g, at least about 700m 2 / g, at least about 800m 2 / g, at least about 900m 2 / g, or at least about 1000m 2 / g of fluid accessible average Brunauer-Emmett-Teller (BET) surface area.

9. The sorbent particle according to any one of the preceding claims, wherein: The average diameter of the sorbent particles is greater than about 1 mm, greater than about 2 mm, greater than about 3 mm, greater than about 4 mm, or from about 2 mm to about 4 mm.

10. The sorbent particle according to any one of the preceding claims, wherein The adsorbent particles contain SiO2 in an amount on average of at least about 80 wt.%, at least about 85 wt.%, at least about 90 wt.%, at least about 95 wt.%, or at least about 99 wt.%, or at least about 99.9 wt.%, or at least about 99.99 wt.%, based on the total weight of the adsorbent particles.

11. The sorbent particle according to any one of the preceding claims, wherein The sorbent particles further comprise alumina.

12. A system configured to process a fluid substance, the system comprising: A sorbent bed comprising sorbent particles as claimed in any one of the preceding claims.

13. The system of claim 12, wherein: The system is a temperature swing adsorption system.

14. The temperature swing adsorption system according to claim 12, wherein: The temperature swing adsorption system is suitable for adsorbing water and / or C5+ or C6+ components from a fluid substance.

15. The temperature swing adsorption system according to claim 14, wherein: These C5+ or C6+ components include one or more of pentane, hexane, benzene, heptane, octane, nonane, toluene, ethylbenzene, xylene, or neopentane.

16. A natural gas purification system comprising an adsorbent bed comprising the adsorbent particles of any one of claims 1 to 11.

17. An adsorbent bed comprising the adsorbent particles according to any one of claims 1 to 11.

18. A method of treating a fluid material comprising an initial concentration of C5+ or C6+ components, the method comprising contacting the fluid material with the sorbent particles of any one of claims 1 to 11.

19. The method of claim 18, wherein: These C5+ or C6+ components include one or more of pentane, hexane, benzene, heptane, octane, nonane, toluene, ethylbenzene, xylene, or neopentane.

20. The method of claim 18, wherein: These C5+ or C6+ components include one or more of n-C6, n-C7, n-C8, n-C9 or benzene.